Software for clinical data interaction - Gonçalves, Pedro (2013)
Ophthalmology is one of many medical fields that suffer from a poor worldwide resource distribution. While Portugal has approximately 69 ophthalmologists per million inhabitants, there are dozens of countries with only 1 ophthalmologist per million inhabitants. It was this project’s goal to build a prototype of a web application to better distribute these ophthalmic resources between countries. The application focused a potential business opportunity from BlueWorks, the creator and host of this project, to provide remote medical exam review to a specific country. The application focused the monitoring program of patients. A monitoring program is a follow up of a disease or condition to evaluate how it is evolving, thus defining which exams will the patient be submitted to and the time gap between examinations. These exams must be evaluated trough a medical consultation with a physician; however, most of the times the disease/condition is stable or following the usual pattern for the disease/condition, which renders the consultation unnecessary. Therefore, these exams are to be evaluated by a foreign physician (using this web application) and he will report whether a consultation is required (due to abnormalities in the evolutionary path of the disease or condition) or it isn’t (disease is stable), in order to try and reduce the work load from these countries with few ophthalmologists. The application was developed using Jboss Seam, a Java WAF (Web Application Framework), deployed on Jboss AS (Application Server) and connected to the DBMS (Database Management System) PostreSQL. The exams were imported into the application (for further review by a foreign ophthalmologist) by integrating OphthalSuite, a software product from BlueWorks that acquires medical exams due to its compatibility with dozens of diagnostic equipment. The integration of OphthalSuite with this application was allowed by Web Service and FTP (File Transfer Protocol) technology. By the end of this project, an application with all of the imposed requirements was accomplished. The final application was validated by submitting it to Scenario tests, based on said requirements.